Hidden black : coherent enhancement of absorption in strongly scattering media - Chong, Yidong (2013)
We show that a weakly absorbing, strongly scattering (white) medium can be made very strongly absorbing at any frequency within its strong-scattering bandwidth by optimizing the input electromagnetic field. For uniform absorption, results from random matrix theory imply that the reflectivity of the medium can be suppressed by a factor ∼(ℓ a /ℓ)N −2 , where N is the number of incident channels and ℓ , ℓ a are the elastic and absorption mean free paths, respectively. It is thus possible to increase absorption from a few percent to >99% . For a localized weak absorber buried in a nonabsorbing scattering medium, we find a large but bounded enhancement.